Mutations in PGRN gene associated with the risk of psoriasis in Pakistan: a case control study - Saima Saleem; Zunaira Imran; Azam Samdani; Bahram Khoso; Sitwat Zehra; Abid Azhar (BMC, 2023)
Abstract Background Psoriasis is a chronic, autoimmune, papulosquamous skin disorder, characterized by the formation of drop-like papules and silvery-white plaques surrounded by reddened or inflamed skin, existing predominantly on the scalp, knees and elbows. The characteristic inflammation and hyperproliferation of keratinocytes in psoriasis is regulated by progranulin (PGRN), which suppresses the expression and release of inflammatory cytokines, such as TNF-α. Methodology In this study mutation analysis of the PGRN gene was performed by extracting the genomic DNA from blood samples of 171 diagnosed psoriasis patients and controls through standard salting-out method, followed by amplification and sequencing of the targeted region of exon 5-7 of PGRN gene. Results Three single nucleotide polymorphisms, rs25646, rs850713 and a novel point mutation 805A/G were identified in the PGRN gene with significant association with the disease. The variant alleles of the polymorphisms were significantly distributed among cases and controls, and statistical analysis suggested that the mutant genotypes conferred a higher risk of psoriasis development and progression. Multi-SNP haplotype analysis indicated that the CAA (OR = 8.085, 95% CI = 5.16-12.66) and the CAG (OR = 3.204, 95% CI = 1.97-5.21) haplotypes were significantly associated with psoriasis pathogenesis. Conclusions These findings demonstrate that polymorphisms in PGRN might act as potential molecular targets for early diagnosis of psoriasis in susceptible individuals.